A new facile synthesis of ultra fine magnesium oxide nanowires and optical properties - Al-Ghamdi, Ahmed A.; Al-Hazmi, Faten; Alnowaiser, Fowzia; Al-Tuwirqi, Reem M.; Al-Ghamdi, Attieh A.; Alhartomy, Omar A.; Yakuphanoğlu, Fahrettin (Springer, 2012)
One-dimensional metal oxides nanowires like magnesium oxide (MgO) play an important role in several nanotechnological applications. MgO nanowires were synthesized for the first time via hydrothermal route using magnesium acetate and urea at 180 A degrees C for 2 h. The synthesized MgO nanowires were characterized by means of X-ray diffraction (XRD), Fourier transformer Infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS), transmission scanning electron microscopy (TEM) and thermal gravimetric analysis (TGA). The obtained results indicated that the MgO nanowires show a predominant well- crystalline cubic face-centered with an average diameter of 10 nm and an average length of 40 mu m. The optical band gap energy of the sample was found to be 3.45 eV. The sample indicates a broadband PL emission in UV region and exhibits a good photoluminescence behavior for photonic devices applications. It is evaluated that this novel synthetic method is very useful and serves as a facile, direct preparation mild chemical method giving mass production of one dimensional MgO nanowires.
Keywords: nanostructures; chemical synthesis; optical properties